Physical abuse of the elderly: a 4‐year retrospective evaluation in the emergency department. Issue 1 (13th August 2018) - Altintop, Ismail; Tatli, Mehmet
Abstract : Aim: Elderly physical abuse (EPA) is defined as injury or assault to or the restriction of an elderly person. Although EPA is an important social problem, its diagnosis is difficult because of tendency to cover up the event. In this study, patients aged 65 years and over who presented at the emergency department (ED) for forensic reasons and in whom physical abuse was suspected were examined. The aim of this study was to raise ED awareness of EPA and thereby to contribute to treatment plans for these patients in the ED. Methods: The study was conducted over a 4‐year period between January 2013 and January 2017. Patients were selected retrospectively from the hospital information system according to the following criteria: (i) admission to ED with trauma; (ii) aged 65 and older; and (iii) evaluated as having forensic trauma by an ED specialist based on either the patient's history or the specialist's observations and suspicions. Results: The patients included 80 men (69%) and 36 women (31%), with a mean age of 73.92 ± 7.08 years. The length of ED stay was 0–1 h in 27.6% of patients and 1–6 h in 46.6%. When the causes of physical trauma were examined, general assault was seen as the most prevalent, occurring in nearly 63% of the patients. Conclusions: There may be three conclusions for the current study: First, although EPA is a rare problem for patients referred to emergency services, health professionals should be suspicious when examining patients 65 years or older because of the difficulties of diagnosing EPA. Second, in patients with no history of suspicious trauma or suspicious radiological imaging results, EPA is also common. Third, because of the undetected EPA mechanism, patients should be examined forensically in suspicious cases and deaths.